2016
DOI: 10.1177/1471301216639424
|View full text |Cite
|
Sign up to set email alerts
|

The role of music in the lives of older adults with dementia ageing in place: A scoping review

Abstract: The number of people around the world living with dementia is predicted to rise from 44 million to 135 million by 2050. Traditional treatments for dementia have been largely unsuccessful and prompted the emergence of alternative strategies. Music is emerging as an effective therapeutic strategy for older adults with dementia however, most of the work to date has focused on institutions. The purpose of this scoping review was to summarize what is known about the role and impact that music plays in the lives of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 42 publications
0
28
0
1
Order By: Relevance
“…We have identified a range of positive impacts of the programme, which support the potential for approaches based on the creative arts to promote engagement and social interaction for people with dementia, thus increasing levels of wellbeing (Elliott and Gardner, 2016). This was augmented by evidence from unpaid carers and volunteers of participants' enjoyment of the intervention, including a strong desire not to miss any sessions as demonstrated by the following quote: "Mum suffers with pain in her leg, but I said to her last time, 'do you really want to go?'…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…We have identified a range of positive impacts of the programme, which support the potential for approaches based on the creative arts to promote engagement and social interaction for people with dementia, thus increasing levels of wellbeing (Elliott and Gardner, 2016). This was augmented by evidence from unpaid carers and volunteers of participants' enjoyment of the intervention, including a strong desire not to miss any sessions as demonstrated by the following quote: "Mum suffers with pain in her leg, but I said to her last time, 'do you really want to go?'…”
mentioning
confidence: 81%
“…This is thought to be primarily due to the potential for music to reach uninjured parts of the brain, which enables people living with dementia to improve how they interact with people within their environment, and helps alleviate the isolation often attributed to dementia (Gerdner, 2009; Hubbard, Cook, Tester, & Downs, 2002; Sorrell, 2008). A recent review of the literature concluded that music can benefit people with dementia by reducing agitation, improving cognition and enhancing social wellbeing (Elliott & Gardner, 2016). The authors also noted that most of the evidence for the impact of music on people with dementia comes from quantitative research designs, and suggested that a qualitative approach may be more appropriate.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the abstract and article content, we retrieved 11 eligible systematic reviews published since 2015. These included: Elliott and Gardner [10]; Fakhoury et al [11]; Fusar-Poli et al [12]; Gomez-Romero et al [13]; Ing-Randolph, Phillips and Williams [14]; Pedersen et al [15]; Petrovsky, Cacchione and George [16]; Tsoi et al [17]; van der Steen et al [18,19]; and Zhang et al [20].…”
Section: Methodsmentioning
confidence: 99%
“…Cognitive reserve represents a baseline to be preserved as much as possible in slowing the onset of ADRD and has been the goal at the heart of both medical and other therapies that have been developed since its identification. Specific nonpharmacological therapies used as clinical interventions may include music programming (Topo et al, 2004;McDermott, Orrell, & Ridder, 2014;Elliott & Gardner, 2016;Evans, Garabedian, & Bray, 2019), art therapy (Mottram, 2003;Beard, 2011;Chancellor, Duncan & Chatterjee, 2014;Sauer, Fopma-Loy, Kinney, & Lokon, 2016;Moss & O'Neill, 2019), reminiscence therapy (Kim et al, 2006;Haslam et al, 2010;Westerhof, Bohlmeijer, & Webster, 2010;Dempsey et al, 2014;Gonzalez et al, 2015;Critten & Kucirkova, 2019), and performative therapy (Basting, 2009;Basting, Towey, & Rose, 2016), among others. Such therapies not only encourage the preservation of arts-based abilities developed over a lifetime prior to the onset of ADRD, but in some cases offer an opportunity for learning a new skill or building further on existing talent.…”
Section: Defining the Scope Nature And Treatment Of Adrdmentioning
confidence: 99%